Arrangements for greater participation by the private sector in external relations activities (CCS GeorgetownGY, 1993)
Focuses on the developments of the Region's external economic relations and examines the scope for the private sector participation in this process. Looks at the organisation and approach to negotiations. Suggests that the private sector has a role to play in the development of the strategic alliances towards the achievement of the negotiating objectives. Indicates that there is also a need for governments at the national level to consult with the private sector and labour in order to achieve the national position.
DC